Unele reglement[ri privind impedimentele absolute și incompatibilități legale în procesul exercitării dreptului la muncă [Articol] - Romandaș, Nicolae (CEP USM, 2022)
This article is dedicated to absolute and legal incompatibilties in the process of enforcement of the right to work. Initially it was made a delimitation between the notion absolute liability and legal incompatibilities in the process of enforcing the right to work. In this content there was made a reference to the legislation, to the specialty literature, doctrine, Convenention of international labour organization. The research of this subject made us to deduce that the nations of implementation are used as a result of impairment of the legal work capacity or deprivation of capacity to exercise it by final decision of the court legal incompatibilities in the process of enforcing the right to work occur as a result of the establishment of prohibitions by law to practice in certain filds of activity. So it is conditioned by some legal reqeurements. They refer only to certain categories of people and are often specific only to certain positions.
SOME REGULATIONS ON ABSOLUTE IMPEDIMENTS AND LEGAL INCOMPATIBILITIES IN THE PROCESS OF EXERCISING THE RIGHT TO WORK
Keywords: legal capacity to work; rights and obligations; freedom of will; alienated person; incompatibility; special legal incapacity; legal impediments